Kontribusi Perempuan Penjual Ikan Asap Dalam Membantu Perekonomian Keluarga - Herlisna; La Ode Monto Bauto; Aryuni Salpiana Jabar (Universitas Halu Oleo (UHO), 2026)
The purpose of this study was to determine the contribution of female smoked fish sellers to supporting the family economy and to identify factors that encourage women to work as smoked fish sellers in Malalanda Village, Kulisusu District, North Buton Regency. This study used a qualitative approach. The informants in this study were the Malalanda Village Head who was willing to provide information and female smoked fish sellers. The informants were determined using a purposive sampling technique. Data sources used in this study included primary and secondary data. Data collection methods used were documentation, observation, and surveys. Data analysis techniques were carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the contribution of female smoked fish sellers is able to improve the family economy and meet the family's daily living expenses. The factors that encourage women to work as smoked fish sellers are the family's low economic condition and the low level of education.